INTRODUCTION TO VOLUME 5 : 2007 - Hashim, Norliza (PLANNING MALAYSIA, 2016)
MIP is once again proud to produce its fifth volume of Planning Malaysia. It is indeed a great achievement to the Institute as we strive to encourage members to write and share new ideas on planning and urban development. The wide ranging topics in this journal reflect the various dimensions of urban planning that is holistic and comprehensive. One of the key objectives of this journal is to provide a platform for town planners to share new ideas and experiences on urban planning. Such new ideas are by research, studies undertaken or actual hands-on experiences of planners. Thus we hope this journal provides a better insight to all readers of the broad dimensions that urban or town planning has and the role town planners play in growth and development of the nation. Planning Malaysia is Malaysian Institute of Planners gift to the industry and to date we have extended the journal to various planning related organizations, institutions of higher learning as well as to all members of the Institute. We hope to eventually extend the circulation of this journal to non-planning related organisations and institutions that play an indirect role in planning within and outside the country as we hope to share the Malaysian experience with as many others. Congratulations once again to the Editor-in-Chief, Dr Alias Abdullah and his team of Editorial Board for the dedication and continuous support to the Institute Thank you.